2019
DOI: 10.1108/jmd-01-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job insecurity on employees’ job outcomes: the mediating role of job embeddedness

Abstract: Purpose Drawing on job embeddedness (JE) and reformulation of attitude theories, the purpose of this paper is to propose a conceptual model in which JE mediates the influence of job insecurity (JIS) on quitting intentions and service recovery performance (SRP). Design/methodology/approach Data came from 313 hotel service workers based on three waves through a two-week period in Iran. Service workers’ SRP was rated by their direct supervisors. The abovementioned linkages were gauged using structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…Consistent with the expectations and previous studies’ results [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ], job insecurity was found to reduce job embeddedness, reinforce the turnover intention, and promote employees’ unethical organizational behavior. However, there are scarce studies conducted in non-Western countries on these relationships [ 75 ].…”
Section: Discussion and Contributionssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the expectations and previous studies’ results [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ], job insecurity was found to reduce job embeddedness, reinforce the turnover intention, and promote employees’ unethical organizational behavior. However, there are scarce studies conducted in non-Western countries on these relationships [ 75 ].…”
Section: Discussion and Contributionssupporting
confidence: 91%
“…Following [ 74 , 78 ], job insecurity was found to have a negative impact on employee embeddedness to the organizations, especially amid the COVID-19 pandemic. When employees feel the risk of future job loss and insecurity, they begin to reconsider their job and their future career path in the company [ 32 ].…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…It has been investigated in the fields of marketing, organizational behavior, air transport management, hospitality and tourism management, and human resource management, e.g., [15,[21][22][23]. Studies illustrate that employees who are high on JE have proclivity to stay with the employer, display better task performance, and are service recovery performers at work, e.g., [24][25][26][27]. Since the turnover of cabin attendants is more than that of other professionals [28], examining the antecedents and outcomes of JE in an industry where cabin attendants display (in)voluntary turnover is important.…”
Section: Relevance and Significance Of The Empirical Studymentioning
confidence: 99%
“…The drop-off and pick-up method is one of the wellestablished data collection methods. It has been widely used by previous tourism and hospitality scholars (e.g., Mwesiumo & Halpern, 2018;Safavi & Karatepe, 2019;Said & Tanova, 2021). Applying the drop-off and pickup method helped confirm tour operators' eligibility and reduce the potential for non-response bias.…”
Section: Sample and Data Collectionmentioning
confidence: 99%